Tasting Life. A Teenage Novel and a Report on the Prosess of Writing it - Þórný Sigurjónsdóttir 1984- (2011)
Tasting Life is a paranormal teenage novel of 107 pages and approximately 39000 words. An outline of the story goes as follows: sixteen year old Hilma, living in Reykjavík city, has lost her best friend Kjartan and wants nothing more than to have him back in her life. Kjartan on the other hand is in such emotional uproar that he is sure that Hilma deserves a better friend. When Fjalar intrudes into their lives he changes them dramatically; he becomes Hilma’s boyfriend and provokes Kjartan against his father. Hilma must show that she is a strong and independent person in order to have Kjartan fully back in her life. Tasting Life is a story about love, passion, friendship, betrayal and family relationships. The novel digs into issues such as sexual desire, power and the importance of food. In the essay I go through the process of writing Tasting Life. The essay is written as a report on the novel, so to understand the content of this essay fully I go out from the assumption that the reader has read the novel before digging into the essay. I begin the report with introducing how I got the idea for the novel and then I go on explaining how I started writing it. My main tool for writing the story were the three creative writing courses I took during my MA studies, but especially the last one I attended in the fall 2011, taught by Anna Heiða Pálsdóttir. Sol Stein’s book Sol Stein on Writing was the main reading material in the course as well as my guide in writing the novel and the essay. In the third chapter I show how the characters came to life and how they are fully in charge of the plot. There after I go into why I chose Reykjavík as the setting for my story and my exploration of the different places in the city so as to make the story accurate. Next I show how and why I wanted my characters to be physical and sexual and there after I explain the concept of food in the novel. In the conclusion I go through the process of editing the novel and what I have learned and acquired by finishing the task of writing ...